Works - Concepts - Processes - Situations - Information. - Galerie Hans Mayer, Düsseldorf (Düsseldorf : Galerie Hans Mayer, 1989)
Armleder, John ; Belcher, Alan ; Bolande, Jennifer ; Brenner, Beth ; Corris, Michael ; Di Benedetto, Steve ; Halley, Peter ; Information Fiction Publicité ; Jaar, Alfredo ; Koons, Jeff ; Lavier, Bertrand ; Lawler, Louise ; McCaslin, Matthew ; Milani, Richard ; Minter, Marilyn ; Mosset, Olivier ; Nagy, Peter ; etc.
Works - Concepts - Processes - Situations - Information, Galerie Hans Mayer, Düsseldorf, November 1988 - January 1989
boek